The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2019
DOI: 10.1123/wspaj.2017-0019
|View full text |Cite
|
Sign up to set email alerts
|

Back to Netball: Motivations for Participation in a Female-Focused Netball Sport Program

Abstract: Back to Netball: Motivations for participation in a female focused Netball sport program.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
6
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(6 citation statements)
references
References 32 publications
0
6
0
Order By: Relevance
“…Results also complement the findings of di Fronso et al (2020) who found female Italian athletes reported higher perceived stress and dysfunctional psychobiosocial states compared to men during lockdown. Females report strong social motives for sports participation ( Whitehead et al, 2019 ) and therefore the loss of sports engagement during lockdown will have also impacted social opportunities, negatively affecting quality of life. Similarly, team sport athletes show higher social or affiliation motivations for exercise engagement ( Molanorouzi et al, 2015 ) suggesting that their participation revolves around interactive elements of training/competition.…”
Section: Discussionmentioning
confidence: 99%
“…Results also complement the findings of di Fronso et al (2020) who found female Italian athletes reported higher perceived stress and dysfunctional psychobiosocial states compared to men during lockdown. Females report strong social motives for sports participation ( Whitehead et al, 2019 ) and therefore the loss of sports engagement during lockdown will have also impacted social opportunities, negatively affecting quality of life. Similarly, team sport athletes show higher social or affiliation motivations for exercise engagement ( Molanorouzi et al, 2015 ) suggesting that their participation revolves around interactive elements of training/competition.…”
Section: Discussionmentioning
confidence: 99%
“…While individual sport participants spent less time sitting in recreational computer use and television viewing, team sport participants spent less time on sedentary socialising or hobbies. This could be explained because team sport traditionally stimulates social engagement [41,42], which replaces the sedentary social activities among adolescents [43].…”
Section: Discussionmentioning
confidence: 99%
“…Although team sports offer an opportunity for socialisation and an enjoyable environment [78], many women do not find competitive PA attractive and prefer to focus on the social, physical, and psychological benefits [79,80]. Many programmes have been conducted to promote PA among women by using a variety of activities, with positive results [81][82][83][84]. Therefore, although activity type may influence participation, it is important to also consider factors such as intensity, frequency, or the physical and social environment where it takes place.…”
Section: Dimension 3 Active Women and Motives For And Types Of Ltpamentioning
confidence: 99%